EDUCATIONAL ENVIRONMENT CONTRIBUTING TO DEVELOPMENT OF COGNITIVE ACTIVITY OF STUDENTS WITHIN THE CREDIT SYSTEM OF EDUCATION - Smagliy, T.I.; Smagliy, T.A. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The article is devoted to the urgent issue of development of cognitive activity of students within the credit system. It describes such integral parts of educational environment leading to the effective formation of students' cognitive activity as high-quality information support of the educational process, inclusion of students and teachers in classroom interaction and extracurricular activities, engagement of students in self-education.
Keywords: cognitive activity; self-education; credit system; information support; quality of education; interaction; educational environment